Cavitation-enhanced delivery of macromolecules into an obstructed vessel. - Rifai, B; Arvanitis, C; Bazan-Peregrino, M; Coussios, C (2010)
Poor drug penetration through tumor tissue has emerged as a fundamental obstacle to cancer therapy. The aim of this study was to examine the ability of cavitation instigated by high-intensity focused ultrasound (HIFU) to increase convective transport of a model therapeutic in an in vitro tumor model. Cavitation activity was quantified by analyzing passively recorded acoustic emissions, and mass transfer was quantified using post-treatment image analysis of the distribution of a dye-labeled macromolecule. The strong correlation between cavitation activity and drug delivery suggests the potential for non-invasive treatment and monitoring.